국내 포도나무 혹병(Agrobacterium vitis) 균주의 유전적 다양성 - 김종군(Jong-Kun Kim); 최재을(Jae-Eul Choi); 강희완(Hee-Wan Kang) (Sigmulbyeong yeon'gu, 2007)
Fifty nine strains of Agrobacterium vitis, the causal agent of crown-gall disease on grapevine, originating from different geographical regions and 16 grapevine cultivars including 35 Kyoho cultivar of Korea, were characterized by PCR polymorphic analysis using Universal Rice Primer(URP). Of 12 URP primers, primers URP1F, URP2R, URP2F, and URP4R, URP17R were available for detecting PCR polymorphic bands among the A. vitis strains. PCR polymorphic bands produced by primers URP2F and URP17R were profiled to 12 strain types. A. vitis strains originated from Kyoho cultivar of grapevine showed relatively simple genetic diversify of the four PCR types, while the A. vitis strains originated from other grapevine cultivars and type culture strains showed various genetic diversity with 8 types. Unweighted Pair-Group Method with Arithmetic mean(UPGMA) cluster analysis using the URP-PCR polymorphic bands showed 59.4. vitis strains are genetically clustered into large seven groups. 거봉 포도나무에 혹병을 일으키는 A. vitis 균주간의 DNA 다양성 평가를 하기 위하여 12종류의 URP primer 적용 성을 조사한 결과 URP1F, URP2F, URP2R, URP4R, URP17R primer가 균주 간 DNA 다형성검정에 유용하였다. 국내외에서 분리한 59 A. vitis 균주를 URP-PCR 증폭하였던 바 균주간의 매우 다양한 PCR 다형성 밴드를 형성 하였으며 12 strain type으로 나눌 수 있었으며 거봉포도로부터 분리된 A. vitis 균주는 4 strain type의 비교적 단순한 유전적 다양성으로 나타났으나, 거봉이외의 다른 포도 품종이나 국외에서 도입된 A. vitis 균주는 8 strain type의 많은 유전적 다양성을 보여 거봉품종 유래 국내 균주와는 PCR 다형성 type에 있어 차이점을 보였다. URP-PCR 다형성 밴드를 집괴 분석하여 UPGMA dendrogram을 작성한 결과 7개의 대 Group으로 분류할 수 있었으며, 그룹 간에는 $62{\sim}100$%까지 다양한 유전적 유사성이 나타났다.